Empagliflozin: a path from glycemic control to reduced cardiovascular mortality and heart failure-related hospitalizations - N. R. Khasanov (Российский кардиологический журнал)
In the EMPA-REG OUTCOME, CANVAS and DECLARE-TIMI 58 studies, in patients with type 2 diabetes and established cardiovascular diseases or risk factors, a decrease in the risk of cardiovascular events and development or worsening of heart failure course without an increase in hypoglycemia incidence was revealed in those receiving sodium-glucose co-transporter-2 (SGLT2) inhibitors compared with placebo. To date, various mechanisms of action of SGLT2 inhibitors have been described, which are considered from the standpoint of their influence on the course and prognosis of heart failure. In the EMPEROR-Reduced study in the group of patients receiving empagliflozin, a significant reduction in the risk of cardiovascular death and hospitalizations for heart failure, regardless of the type 2 diabetes presence, was revealed.